Numerical simulation for external magnetic field influence on Fe3O4-water nanofluid forced convection. Issue 4 (11th June 2018) - Sheikholeslami, Mohsen
Abstract : Purpose: The purpose of this paper is to simulate nanofluid laminar steady flow in a lid-driven porous cavity under the impact of Lorentz forces. Design/methodology/approach: Shape effect of nanoparticles and magnetic field impact on nanofluid properties are taken into consideration. The solutions of final equations are obtained by control volume based finite element method (CVFEM). Findings: Graphs are depicted for different values of Darcy number, Fe3 O4 -water volume fraction, Reynolds and Hartmann numbers. Originality/value: Results illustrated that using Platelet-shaped nanoparticles results in the highest Nusselt number. Nusselt number augments with rise of Darcy and Reynolds number.